2020
DOI: 10.3390/agronomy10121952
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Meat and Bone Meal (MBM) on the Seed Yield and Quality of Winter Oilseed Rape

Abstract: The aim of a two-year field experiment conducted in north-eastern (NE) Poland was to evaluate the effect of meat and bone meal (MBM) applied without or with mineral nitrogen (N) on seed yield, thousand seed weight (TSW), protein yield, fat yield, fatty acid profile and glucosinolate (GLS) concentrations in winter oilseed rape. Five treatments were compared: MBM applied at 1.0, 1.5, 2.0 Mg ha−1, inorganic NPK, and a zero-N check. The first two MBM plots and the NPK plots received supplemental inorganic N to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Nogalska and Załuszniewska [18] analyzed macronutrient (N, P, K, Ca, and Mg) concentrations in winter oilseed rape seeds and straw and their uptake by aboveground biomass (two-year means). Załuszniewska and Nogalska [19] determined seed yield, thousand seed weight, protein yield, fat yield, fatty acid profile, and glucosinolate concentrations in winter oilseed rape (two-year means). In the present study, data on winter oilseed rape (seed yield, straw yield, N content and uptake) were subjected to one-way analysis of variance (ANOVA) separately for each year (Section 2.7), similarly to data on maize and winter wheat, which were grown in a six-year crop rotation system on the same 20 plots; plot size was 20 m 2 (4 m × 5 m).…”
Section: Crop Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nogalska and Załuszniewska [18] analyzed macronutrient (N, P, K, Ca, and Mg) concentrations in winter oilseed rape seeds and straw and their uptake by aboveground biomass (two-year means). Załuszniewska and Nogalska [19] determined seed yield, thousand seed weight, protein yield, fat yield, fatty acid profile, and glucosinolate concentrations in winter oilseed rape (two-year means). In the present study, data on winter oilseed rape (seed yield, straw yield, N content and uptake) were subjected to one-way analysis of variance (ANOVA) separately for each year (Section 2.7), similarly to data on maize and winter wheat, which were grown in a six-year crop rotation system on the same 20 plots; plot size was 20 m 2 (4 m × 5 m).…”
Section: Crop Plantsmentioning
confidence: 99%
“…Long-term field experiments produce the most reliable results in terms of soil chemism and productivity, i.e., the yield and quality of agricultural crops. Some of the results relating to winter oilseed rape have already been published [18,19], as mentioned in the Materials and Methods section (Section 2.3). A research article describing the P content of plants and soil is currently being prepared for publication.…”
Section: Introductionmentioning
confidence: 99%
“…This study is part of long-term research (a six-year field experiment) investigating the influence of MBM on yield components, the chemical composition of crops, and selected properties of soil. The results regarding the yield and quality of winter oilseed rape [13,14]; the yields and N content of silage maize, winter wheat, and oilseed rape; and soil N balance [15] have already been published.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain PHs on the industrial scale, these materials are subjected to chemical, thermal and enzymatic hydrolysis [14]. It is worth noticing that animal collagen recently became an object of scientific interest due to its practical application allowing reduction in mineral fertilization and disposal of animal-processing wastes [11,15,16]. It was showed that PHbased biostimulants can improve agricultural production and satisfy global demands for environment-friendly crop management practices [17,18].…”
Section: Introductionmentioning
confidence: 99%